Diagnostic Laparoscopy to assess tubal and pelvic pathology in patients of subfertility: A retrospective analysis - Subedi, Nilam; Ghimire, Asmita; Pant, Padam Raj (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To assess the tubal pathology contributing to primary and secondary infertility by laparoscopic examination. Methods: The study was carried out in the department of Obstetrics and gynecology, Grande International Hospital. This is a retrospective study conducted in tertiary care hospital over a period of 2 yrs. From 2020 February to 2022 January. All patients with complaints of infertility (primary and secondary) who were admitted, evaluated and operated for infertility in Obstetrics and Gynaecology department of Grande international Hospital. Results: Of the 52 patients minimum age was 20 and maximum was 46 with mean age of 30.52±4.885. Thirty eight patients had primary infertility and 14 had secondary. Forty patients had normal uterus while 12 had enlarged uterus. Hydrosalpinx was found in 11.5 % and 30.8% in right and left tube respectively. Pyosalpinx was found in 9.6% and 7.7% in right and left tube respectively. Bilateral tubes were patent in 22 cases while bilateral blocked tube was found in 13 cases so rest 17 cases had unilateral tubal block. Pelvic adhesions were found in 44.2 % cases. Most of them were associated with endometriosis (15.4%) followed by ovarian cyst (11.5%) and fibroid uterus (11.5%). Conclusions: Majority had normal tubal pathology followed by edematous tube, hydrosalpinx and pyosalpinx. Endometriosis, fibroid and ovarian cyst were commonly associated conditions.